Effect of aerodynamic interference to tail propeller on a compound helicopter - Kimura, K.; Sugawara, H.; Tanabe, Y. (My University, 2021)
Computational Fluid Dynamics (CFD) simulations are conducted focusing on a tail propeller on a conceptual model of a high-speed compound helicopter proposed by JAXA. Since a number of components such as fixed wing and propellers are added to a conventional helicopter, it is important to understand the aerodynamic interactions between the components. In this paper, the influence of aerodynamic interactions on the performance of the tail propeller with the main rotor and fuselage, and the influence on the fuselage drag from the tail propeller, are investigated. The propeller performance tends to improve when subjected to the main rotor wake, however, the effect becomes trivial as the advance ratio increases. As for the interaction between the fuselage and the propeller, it is shown that the propeller performance placed in the shadow of a fuselage improves instead of increasing the drag of the fuselage due to the induced flow by the propeller. After considering these conflicting effects, it was found that although they cancel each other out in terms of thrust and drag, the propeller efficiency itself has a large possibility of decreasing during high-speed flight